The ?-Statistical Convergence in Riesz Spaces - Aydin, Abdullah; Cinar, Muhammed; Et, Mikail (Maik Nauka/Interperiodica/Springer, 2021)
We introduce the lambda-statistical monotone and the lambda-statistical order convergent sequences in Riesz spaces. We also give some relations between the lattice operations and the lambda-statistical convergence in Riesz spaces, and also, some relations between the order convergence and lambda-statistical order convergence.
Keywords: lambda-statistical monotone; lambda-statistical order convergence; statistical convergence; Riesz space; order convergence